Dark exposure affects plasticity‐related molecules and interneurons throughout the visual system during adulthood. Issue 8 (11th December 2019) - Carceller, Hector; Guirado, Ramon; Nacher, Juan
Abstract: Several experimental manipulations, including visual deprivation, are able to induce critical period‐like plasticity in the visual cortex of adult animals. In this regard, many studies have analyzed the effects of dark exposure in adult animals, but still little is known about the role of interneurons and plasticity‐related molecules on such mechanisms. In this study, we analyzed the effects of 10 days of dark exposure on the connectivity and structure of interneurons, both in the primary visual cortex and in the rest of cerebral regions implicated in the transmission of visual stimulus. We found that this environmental manipulation induces changes in the expression of synaptic molecules throughout the visual pathway and in the structure of interneurons in the primary visual cortex. Moreover, we found altered expression in the polysialylated form of the neural cell adhesion molecule and in perineuronal nets surrounding parvalbumin expressing interneurons, suggesting that these plasticity‐related molecules may be involved in the changes produced by dark exposure. Together, our findings indicate that dark exposure produces an important alteration of inhibitory circuits and molecules related to their plasticity, not only in the visual cortex but throughout the visual pathway. Abstract : Ten days of dark exposure during adulthood have an important impact on the microcircuitry of the primary visual cortex, especially on its interneurons. This paradigm induced changes in the expression of synaptic molecules and in the structure of Martinotti interneurons. It also altered the expression of the polysialylated form of the neural cell adhesion molecule and induced changes in the perineuronal nets surrounding parvalbumin expressing interneurons, suggesting that these plasticity‐related molecules may be involved in the changes produced by dark exposure. Some of these changes are also observed throughout the visual pathway.